Spectrophotometric Determination for Metronidazole drug in pharmaceutical form (tablet) by Multi-wavelengths method - Mumin Fareed Hamad Al-Samarrai (Tikrit Journal of Pure Science, 2023)
The research includes, spectrophotometric determination for Metronidazole drug (MND) in pharmaceutical form (tablet), using multi-wavelengths technique, the results obeyed Beer’s law in the concentration ranges of between (0.5-25 µg.ml-1), recovery percentage Rec% (99.99- 100.05), RSD% (0.0011-0.0019), and detection limit (0.2042-2.9772 µg.ml-1) This method been successfully applied to the determination of MND in pharmaceutical form tablet. The results also showed there is no interference from additives.